2011
DOI: 10.4049/jimmunol.1100917
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Boosts Proinflammatory Outcome of Antiviral Response in Human Cells

Abstract: Excessive inflammation during bacterial and viral infections is destructive to the host and involves elevated production of proinflammatory cytokines. It is especially deleterious in organs with space constraints such as lung and the CNS. Indeed, a number of viruses that infect lungs, such as avian influenza virus, SARS-associated coronavirus, and respiratory syncytial virus, elicit a very high level of proinflammatory cytokines; however, it is unclear what triggers their production. In this study, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 39 publications
(41 reference statements)
4
71
1
1
Order By: Relevance
“…The discovery that the TIR domain of TLRs and IL-1Rs and the SEFIR domain of IL-17Rs are part of a larger domain superfamily highlights the importance of such a motif in innate immune signalling 31 . While a previous report indicated that IL-17R signalling can co-operate in a positive manner with some TLRs 47 , we now propose that the IL-17RD-SEFIR domain negatively regulates TIR domain-containing TLRs, and the region of the IL-17RD-SEFIR domain that corresponds to box 3 of TIR domains is central to this function. It is also noteworthy that mutation of a highly conserved threonine residue in this region abolished the functional effects of the IL-17RD SEFIR domain, and it will be interesting to assess whether this residue is subject to phosphorylation and thus regulation by posttranslational modification.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The discovery that the TIR domain of TLRs and IL-1Rs and the SEFIR domain of IL-17Rs are part of a larger domain superfamily highlights the importance of such a motif in innate immune signalling 31 . While a previous report indicated that IL-17R signalling can co-operate in a positive manner with some TLRs 47 , we now propose that the IL-17RD-SEFIR domain negatively regulates TIR domain-containing TLRs, and the region of the IL-17RD-SEFIR domain that corresponds to box 3 of TIR domains is central to this function. It is also noteworthy that mutation of a highly conserved threonine residue in this region abolished the functional effects of the IL-17RD SEFIR domain, and it will be interesting to assess whether this residue is subject to phosphorylation and thus regulation by posttranslational modification.…”
Section: Discussionmentioning
confidence: 94%
“…Recent findings have shown that IKKi and TBK1, key kinases in activating IRFs and regulating type-I IFN expression, regulate IL-17 signalling by directly phosphorylating the adaptor molecule Act1 (refs 48,49). In addition, IL-17 is produced in response to avian influenza virus and respiratory syncytial virus and synergizes with anti-viral signalling pathways 47 . These discoveries demonstrate the growing complexity of IL-17 signalling and its impact on other signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the lack of robust IL-17A and IL-22 production in the lungs of Cl 2 -exposed mice after microbial challenge suggests that a component of Cl 2 -induced immunosuppression is lower induction of soluble antimicrobial factors via the IL-17A and IL-22 axis. Since IL-17A and IL-22 are essential effector cytokines that coordinate the immune response to multiple lung pathogens, including A. fumigatus (26,61), influenza (33,46), Pseudomonas aeruginosa (15), Klebsiella pneumonia (4), and Staphylococcus aureus (17,32), our finding has broad implications for lung host defense mechanisms impaired by Cl 2 gas exposure (and potentially other agents that target the respiratory tract).…”
Section: Discussionmentioning
confidence: 99%
“…Marked synergy in induction of gene expression has been observed with other inflammatory stimuli, e.g. TNF (9,10) or poly(I:C) (11). The IL-17 family contains several isoforms that homo-or heterodimerize and bind to members of a distinct family of IL-17 receptors.…”
mentioning
confidence: 99%